Collaborative Governance for Social Change and Environmental Sustainability: A Case Study of Campania Region - Zubair Ahmad; Paolo Esposito (Administrative Sciences)
The emphasis on collaborative governance and effective leadership to bring any social change is gaining prominence among researchers. This study investigates how leadership and collaborative governance can drive social change in waste management in Campania, using a qualitative, multi-site case study approach. Interviews of relevant politicians, public managers, citizens, waste management organizations and academics were conducted (2023–2024). This research uses the lens of multiple theoretical frameworks such as collaborative governance, network agency, public value framework and transformational leadership to explore different dynamics of the research such as stakeholder engagement, public value creation and leadership effectiveness in waste management. Moreover, several obstacles in the way of achieving social change in Campania concerning waste management and environmental sustainability are identified. The findings of this study added to the theoretical understanding of collaborative governance and social change through the demonstration of how transformational leadership, stakeholder participation and trust-based relationships drive good waste management while identifying structural limitations such as corruption and organized crime that hindered governance. Practically, it highlights five interconnected themes from interviews of leadership that civic leaders and managers must establish to promote positive social change: Difficulties in leadership effectiveness, civic potential unused, media mobilization, hope for a miracle and stakeholder engagement diversification. The public value framework is used to analyze the potential role of leadership in bringing change in society. The research findings are replicable and can be applied to a similar set of circumstances. This study advances existing research by addressing the gap in understanding how collaborative governance and transformational leadership can be integrated to tackle waste management and environmental sustainability challenges. The findings can be applied to other regions facing similar governance challenges, making it relevant for global sustainability efforts. Italy’s government has green-lighted projects to make these activities more visible while downplaying their negative impacts on the environment and public health.